2014
DOI: 10.1158/1535-7163.mct-14-0052
|View full text |Cite|
|
Sign up to set email alerts
|

Paclitaxel-Loaded PEG-PE–Based Micellar Nanopreparations Targeted with Tumor-Specific Landscape Phage Fusion Protein Enhance Apoptosis and Efficiently Reduce Tumors

Abstract: In an effort to improve the therapeutic index of cancer chemotherapy, we developed an advanced nanopreparation based on the combination of landscape phage display to obtain new targeting ligands with micellar nanoparticles for tumor targeting of water insoluble neoplastic agents. With paclitaxel as a drug, this self-assembled nanopreparation composed of MCF-7-specific phage protein and polyethylene glycol phosphatidyl ethanolamine (PEG- PE) micelles showed selective toxicity to target cancer cells rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…As NP à base de metais, principalmente de zinco, apresentam significantes efeitos geradores de autofagia que facilitam e potencializam os efeitos causados pela ERO e, consequentemente, induzem com maior facilidade a morte de células cancerígenas, também causada pela flexibilidade das moléculas de zinco, o que as tornam ótimas moléculas carreadoras também 21,30,31 .…”
Section: Resultsunclassified
“…As NP à base de metais, principalmente de zinco, apresentam significantes efeitos geradores de autofagia que facilitam e potencializam os efeitos causados pela ERO e, consequentemente, induzem com maior facilidade a morte de células cancerígenas, também causada pela flexibilidade das moléculas de zinco, o que as tornam ótimas moléculas carreadoras também 21,30,31 .…”
Section: Resultsunclassified
“…Furthermore, the described system may also represent a promising platform in cancer therapy, since it presents a great potential for carrying and delivering hydrophobic drugs, in special for fenestrated tissues, such as solid tumors. Moreover, other contrast agents, such as Gadolinium (for magnetic resonance imaging [47]) can be easily associated in the DTPA portion of the PM developed. Another possibility for the proposed system is its functionalization for active targeting purposes for specific tumors [48].…”
Section: Discussionmentioning
confidence: 99%
“…Since surface nucleolin is overexpressed in a number of tumor and tumorsurrounding cells, the promiscuity of the DMPGTVLP peptide may expend to various cancer cells and cells of tumor microenvironment, such as activated lymphocytes, angiogenic endothelial cells within the tumor vasculature and others [39]. It was shown to enhance antitumor activity of the phage-navigating nanomedicines in mice tumor models [40,41]. Promiscuous peptides of the first type have been selected in the intercellular selection scheme [32] ( Figure 2B).…”
Section: Promiscous Peptides and Proteins: Potential Navigating Sensorsmentioning
confidence: 99%
“…It was demonstrated that phage fusion proteins selectively interacting with various cellular phenotypes are ideal construction material for preparation of targeted nanomedicine platforms with increased antitumor potential toward human prostate, breast, lung and pancreatic cancer cells [40,41,81]. It was shown that the cell-binding specificity of selected phages and their proteins translates [40,90]. (B) Incorporation of major coat proteins p8 into the growing phage (The model is adapted with permission from [91] C Elsevier [1998]).…”
Section: The Major Coat Protein Of Landscape Phages As Antenna Of Tummentioning
confidence: 99%